Faculty development strategies based on the development and innovation programs of medical education (qualitative research) - Maryam Gaemi Amiri; Abasalt Khorasani; Mohammad Yamani Douzi Sorkhabi; Shahram Yazdani (Babol University of Medical Sciences, 2017)
BACKGROUND AND OBJECTIVE: The development and innovation program in medical education is a strategic program in order to fulfill the objectives of the developmental programs of the health system. Since the medical faculty members have an important role in promoting public health, this study aimed to identify strategies for growth and development of faculty members of medical universities at northern part of Iran based on the evolution and innovation program of medical education in the form of grounded theory. METHODS: This qualitative study was conducted using Grounded Theory Approach during 2015-2016. The study population included 22 faculty members of medical universities at the northern part of Iran. Sampling was performed by targeted method on those who were responsible in university or college. They were asked about the strategies for faculty development based on the development and innovation program in medical education. FINDINGS: The results of collected data were classified into two main themes: Health ministry strategies (institutionalization of accountable and justice-centered education), and academic strategies (supporting the medical education development centers) and 9 sub-themes. CONCLUSION: Considering the results of the study, it is recommended to Education policy makers to design and provide a more accurate and systematic programs in order to achieve development and growth of their faculty members according to the evolution and innovation program in medical education; so, the effectiveness and efficiency of faculty members and consequently the higher education system will be improved.